Characterization of a latent thermal energy storage heat exchanger using a charging time energy fraction method with a heat loss model. (25th January 2023) - Couvreur, Kenny; Beyne, Wim; Tassenoy, Robin; Lecompte, Steven; De Paepe, Michel
Highlights: The charging time energy fraction method is extended with a heat loss model. A finite volume model is used to validate the proposed heat loss model. A shell and tube latent thermal energy storage system has been characterized. The outlet state is predicted within measurement uncertainty except for the start-up. Abstract: Correlations predicting the transient behavior of latent heat thermal energy storage systems without too many computational efforts are valuable for engineering practices. This characterization of latent heat thermal energy storage systems can be done with the recently developed charging time energy fraction method. This method allows fitting a predictive model for the outlet heat transfer fluid temperature of a latent thermal storage unit as a function of the input condition. The previous application of the method neglected heat transfer to the ambient. The present paper improves the charging time energy fraction method by proposing a heat loss model to the charging time energy fraction model. A finite volume model of a high-temperature thermal battery is used to validate the proposed heat loss model. The improved charging time energy fraction method is then used to characterize a high-temperature thermal battery by calibrating a model on 36 numerical charging experiments. The charging time prediction between energy fractions of 0 and 0.96 deviates maximally 2 % from the measured charging time over all 36 calibration experiments. The deviation increases near the end of the charging process, especially for slower charging experiments. Across the 36 calibration experiments, the worst prediction has an average absolute temperature difference of 0.50 °C with a maximum deviation of 2.58 °C at the very beginning of the charging where fast transients are occurring. The calibrated model is also compared to four numerical validation experiments and four real experiments. Overall it is shown that this low computational cost model with average calculation times of 2–3 ms can accurately predict the heat transfer fluid outlet temperature of latent thermal energy storage heat exchangers.